Rapid detection of heavy metals - Lai, Alson Zhi Jie (Nanyang Technological University, 2021)
Heavy metals, such as cadmium, lead and arsenic are the most significant inorganic contaminants due to their persistence in the environment and the major health risk they posed to the human health. Prolong toxic accumulation of heavy metals in the human body has been known to cause complications such as kidney damage, brain damage and respiratory failure. In this project, samples of varying concentration and mixture of heavy metals are tested using voltammetry test. The goal is to develop a system that is capable or carrying out rapid waste material testing and in-situ water analysis. [1st Award]